Exploring the Relationship between HSV-2/HIV Co-Infection and Health-Related Quality of Life of Adult HIV-Positive Women: A Mixed Methods Study - Ion, Bridget Allyson (My University, 2010)
Background: The life-time prevalence ofHSV-2 is higher in people infected with HIV/AIDS compared to the general population. Little is known about the experiences of women living with these two chronic sexually transmitted viral infections (STVIs), for example, whether HSV-21 HIV co-infection complicates women's experiences and influences their perceived health-related quality of life (HRQoL). The degree to which HSV-2/HIV co-infection changes perceived physical and mental HRQoL ofHIV-positive women when taking into account other factors related to HRQoL including the degree of immunosuppression, demographic characteristics, and co-existent psychological issues is not known. It has not been investigated whether these two chronic STVIs create additional challenges in social and sexual relationships for women. It is also not understood if body image or self-esteem are complicated by HSV-2IHIV co-infection, as well as how women perceive and experience disclosure in relationships and stigma. No quantitative or qualitative studies have explored these phenomena in a Canadian HIVpositive female population.
Methods: This mixed methods study explored the association between HIVI HSV-2 coinfection and physical and mental HRQoL of adult HIV -positive women. A sequential exploratory model was utilized, which involved collecting qualitative data after a quantitative phase. In the first quantitative phase, a cross-sectional questionnaire was administered, HSV -2 sero-status was determined and clinical correlates and HRQoL scores were analyzed using multivariable methods. The second qualitative phase was conducted to further explain the quantitative findings; participants' views of the relationship between symptomatic HSV-2 and HIV co-infection and HRQoL were explored. The qualitative phase employed an interpretive phenomenological philosophy and methodology.
Quantitative Findings: Although women's HRQoL scores on general and HIV-specific measures differed depending on their HSV-2 sero-status, place of origin, receipt of antiretroviral therapy, etc., HSV-2/HIV co-infected women did not have significantly different HRQoL scores compared to women infected with HIV alone. This conclusion was drawn on the basis of only fair goodness-of-fit of the linear regression models. HSV -2 sero-positivity predicting a better perceived physical and mental HRQoL was also considered biologically implausible and divergent with the literature.
Qualitative Findings: The participant narratives highlighted the meaning that women ascribe to living with HIV and HSV-2 in relationship to their perceived HRQoL. HIV was something that affected their global physical and mental HRQoL; it was associated with a social and historical context and was mapped onto their life trajectories. HSV-2, on the other hand, was an immediate concern experienced on an episodic basis, and was more relevant to dimensions of HRQoL such as day-to-day physical and social functioning, as well as intimacy and relationships with partners. HSV-2 infection was a separate, dominant and gendered medical condition that compounded and complicated women's experiences with HIV.
Main implication: HRQoL assessments from the perspective of patients will become increasingly important as life-prolonging antiretroviral treatments are refined and clinicians and HIV -positive individuals look to maximize quality oflife and well-being. As people living with HIV I AIDS continue to face complex health-related challenges, it is essential to incorporate HRQoL into treatment and care planning. It is important for service providers to account for HSV -2 as an important medical and psychosocial issue and to discuss with their clients how HSV -2 may affect perceived HRQoL. This study adds to the body of knowledge regarding women's experiences living with HN, but adds an important layer regarding co-infections and co-morbidities, which are relevant to developing an understanding of women's sexual health.
Keywords: Biostatistics; Clinical Epidemiology; Biostatistics